Knowledge and practice of standard measures in occupational exposure to blood and body fluids among nurses in a University Hospital in the United Arab Emirates (Italian Journal of Public Health, 2010)
This cross sectional study was conducted to assess the knowledge and practice of preventive measures inoccupational exposure to blood and body fluids among nurses in a university hospital in the UAE. A pre-testedstructured self administered questionnaire was used for data collection. The mean age of the respondentswas 29.59±5.96 years and the median duration of clinical experience was 63 months ranging from 10 monthsto 264 months. Of the total, 25.7% reported having had exposure to splashes of blood and body fluids intothe eyes or mouth. 98% of nurses reported that if there had been any splash of blood or body fluids it isimportant to rinse with plenty of running water. 98% knew that the ideal method of disposal of sharp waste(e.g. hypodermic needles) was to put it in a puncture proof container immediately after use. 93.1% of thenurses reported that the needle pricks, cuts or scratches should be bled by squeezing. 93% habitually usedmasks always during surgery and 80.4% always wore goggles during surgery. With regard to recapping ofneedles, 44.6% were aware that needles should be recapped by single hand technique after use and amongthem 93.3% practiced this method; there was a statistically significant association (p
Keywords: blood and body fluids; nurses; occupational exposure; prevention